Knowledge, beliefs, and acceptability of people toward new COVID-19 vaccines: a pilot study - Amjad Alfaleh; Abdullah Alkattan; Nashwa Radwan; Nagla Mahmoud; Alaa Alageel; Wedad Alanezi; Khaled Alabdulkareem (Taylor & Francis Group, 2021)
A cross-section pilot study was done to determine the knowledge and belief toward new COVID-19 vaccines among a small sample size group of people. A new Vaccine Acceptability Questionnaire (VAQ) consists of 31 questions that were concerned about three elements: underlying factors, knowledge, and beliefs. The study included 96 people from the different regions of Saudi Arabia who had accepted to participate in this pilot study. Around 31% of the included people had low to very low acceptability toward COVID-19 vaccines; however, the other 69% had moderate to high acceptability. The new simple designed questionnaire (VAQ) could be effective in assessing knowledge, beliefs, and acceptability toward COVID-19 vaccination among a specific group of population.